PELATIHAN KEWIRAUSAHAAN BAGI PELAKU UMKM KAB/KOTA DALAM PROVINSI JAMBI DENGAN TEMA “PENYUSUNAN LAPORAN KEUANGAN SEDERHANA” - Neldawaty, Rika; Suherman, Suherman; Hierdawati, Trie; Siswoyo (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
This Community Service Activity is carried out for MSME Actors in Regency/City in Jambi Province. The preparation of company financial reports is carried out in a certain period. Usually companies make financial reports when their company's accounting period enters the end. This accounting period is determined by each company. Some are done at the end of the year, some are done every few months. Through the Simple Financial Report Preparation Training, it is hoped that it will help MSME partners manage their business financial reports. And will increase Capability, namely improving the Recording of Financial Reports and Transactions manually to be fast and accurate. Hopefully, with this preparation training, you will gain insight, knowledge and understanding of the basics of proper financial management and including how to make a budget.